Love's next meeting : the forgotten history of homosexuality and the left in American culture - Lecklider, Aaron (University of California Press, 2021)
How queerness and radical politics intersected--earlier than you thought. Well before Stonewall, a broad cross section of sexual dissidents took advantage of their space on the margins of American society to throw themselves into leftist campaigns. Sensitive already to sexual marginalization, they also saw how class inequality was exacerbated by the Great Depression, witnessing the terrible bread lines and bread riots of the era. They participated in radical labor organizing, sympathized like many with the early prewar Soviet Union, contributed to the Republicans in the Spanish Civil War, opposed US police and state harassment, fought racial discrimination, and aligned themselves with the dispossessed.